2015
DOI: 10.3415/vcot-14-06-0093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intramedullary pin size and monocortical screw configuration on locking compression plate-rod constructs in an in vitro fracture gap model

Abstract: Objective: To investigate the effect of intramedullary (IM) pin size in combination with various monocortical screw configurations on construct stiffness and strength as well as plate stain in locking compression plate-rod (LCPR) constructs. Methods:A synthetic bone model with a 40mm fracture gap was used. LCPs with monocortical locking screws were tested with no pin (LCPMono) and IM pins of 20% (LCPR20), 30% (LCPR30) and 40% (LCPR40) of IM diameter. LCPs with bicortical screws (LCPBi) were also tested in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our results are consistent with a previous canine cadaveric study that found higher bending and torsional stiffness following orthogonal plate application. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with a previous canine cadaveric study that found higher bending and torsional stiffness following orthogonal plate application. 4…”
Section: Discussionmentioning
confidence: 99%
“…1 2 3 Biomechanical reports of orthogonal locking compression plate (LCP) constructs in dogs are limited to conference proceedings of a single canine cadaveric study that investigated orthogonal constructs with a primary 3.5-mm LCP and an orthogonal 2.7-mm LCP and compared stiffness to a single 3.5-mm LCP in axial compression, four-point bending, and axial torsion. 4 In cadaveric feline hemipelves, nonlocking orthogonal constructs had higher bending stiffness and greater resistance to 1-, 2-, and 5-mm gap formation under cyclic testing compared to single plate constructs. 5 Orthogonal LCP constructs have shown higher bending and torsional stiffness and lower plate strain than single plate constructs and adjacent plate constructs in human humerus and femoral models.…”
Section: Introductionmentioning
confidence: 92%